Clinical Factors and Quantitative CT Parameters Associated With ICU Admission in Patients of COVID-19 Pneumonia: A Multicenter Study - Yan, Chengxi; Chang, Ying; Yu, Huan; Xu, Jingxu; Huang, Chencui; Yang, Minglei; Wang, Yiqiao; Wang, Di; Yu, Tian; Wei, Shuqin; Li, Zhenyu; Gong, Feifei; et al. (Frontiers in Public Health, 2021)
Abstract The clinical spectrum of COVID-19 pneumonia is varied. Thus, it is important to identify risk factors at an early stage for predicting deterioration that require transferring the patients to ICU. A retrospective multicenter study was conducted on COVID-19 patients admitted to designated hospitals in China from Jan 17, 2020, to Feb 17, 2020. Clinical presentation, laboratory data, and quantitative CT parameters were also collected. The results showed that increasing risks of ICU admission were associated with age> 60 years old (odds ratio [OR], 12.72; 95% confidence interval [CI], 2.42-24.61; P = 0.032), coexisting conditions (OR, 8.24; 95% CI, 2.15-31.67; P = 0.048) and increased CT derived total opacity percentage (TOP) (OR, 14.84; 95% CI, 1.65-33.41; P = 0.016). In conclusion, older age, coexisting conditions, larger TOP at the time of hospital admission are associated with ICU admission in patients with COVID-19 pneumonia. Early monitoring the progression of the disease and implementing appropriate therapies are warranted.